Prevalence of risk factors for coronary artery disease among cardiac patients in central level hospital. - Aryal,Binita (2016)
ABSTRACT: Coronary artery disease (CAD) is one of the most common causes of mortality and morbidity in both developed and developing countries. CAD becomes third global burdened disease ranked by WHO and leading fatal disease till 2020. A descriptive cross-sectional study was conducted to find out the prevalence of risk factors for coronary artery disease among cardiac patients. Non-probability purposive sampling technique was used to select the coronary artery disease patients with structured questionnaire to identifying prevalence and to collect required information. The data was collected by Face to Face interview method. The obtained data was analyzed using descriptive and inferential statistics. The results of the study revealed the proportion of male and female 64.2% and 35.8% respectively. Of the 106 patients the mean age of the respondents was (58.65±11.26). The most prevalence of risk factors for coronary artery disease of the respondents were dyslipidemia (67.6%), smoking (53.8%), hypertension (47.2%), physically inactive (46.2%), diabetes mellitus (39.6%) and previous history of CAD (38.7%). Likewise, other less common risk factors were obesity (31.1%), alcoholic (19.8%) and family history of CAD (17.9%). In conclusion, coronary artery disease risk factors are highly prevalent among dyslipidemic, smokers and hypertensive patients in this study. As management of risk factor is important aspect in the primary prevention of CAD, these patients are recommended to be trained regarding lifestyle changes. Also, prevention strategies can play an important role in reducing patient morbidity and mortality. Key words: Coronary Artery Disease, Prevalence, Risk Factors, Cardiac Patients